Effect of Upright Posture on Endothelial Function in Women and Men - Habib, Karim; Fallah, Behzad; Edgell, Heather (Frontiers in Physiology, 2022)
Women are more prone to orthostatic intolerance compared to men and have a greater vasodilatory capacity. We investigated the hypothesis that women would have greater peripheral flow-mediated dilation (FMD) while in the upright posture compared to men, which could contribute to this phenomenon. In young healthy women (age: 20 ± 3, BMI: 27 ± 5 kg/m2, n = 10) and men (age = 21 ± 2, BMI: 27 ± 8 kg/m2, n = 8), we assessed FMD of the brachial artery and hemodynamics to determine endothelial function during the supine and 70° head-up tilt postures (randomized). The brachial artery was kept at heart level in both trials. We observed that FMD increased in both sexes during tilt (Women: 11.9 ± 5.3 to 15.7 ± 5.6%; Men: 8.4 ± 3.2 to 14.6 ± 3.4%, Main effect of tilt p = 0.005) which was not due to changes in blood pressure or shear stress. There were no interaction effects between sex and posture. In a second cohort of women (age: 22 ± 3, BMI: 23 ± 3 kg/m2, n = 9) and men (age: 22 ± 2, BMI: 25 ± 8 kg/m2, n = 8), we investigated reactive hyperemia by peripheral arterial tonometry (LnRHI) via EndoPAT. Interestingly, we found that the EndoPAT response was decreased in both sexes during tilt (LnRHI: Men: 0.70 ± 0.28 to 0.59 ± 0.40, Women: 0.52 ± 0.23 to 0.30 ± 0.32, Main effect of tilt p = 0.037). We previously found that FMD is related to coronary responses to acetylcholine and adenosine whereas EndoPAT is related to coronary responses to dobutamine. Therefore, we suggest that sympathetic mediated dilation is attenuated in the upright posture while the increased vasodilatory response as measured by FMD in the tilt posture could be attributed to increasing metabolite production from postural muscles.